2012
DOI: 10.2224/sbp.2012.40.7.1213
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Rejection Experiences and Shame as Predictors of Susceptibility to Peer Pressure Among Korean Children

Abstract: We examined the relationships among parental and peer rejection, shame, and susceptibility to peer pressure during late childhood. A sample of 610 boys and 575 girls from Korea filled out questionnaires and nominated 3 classmates to measure peer rejection. The results showed that shame is the strongest predictor of susceptibility to peer pressure, and shame provided a pathway by which interpersonal rejection was related to susceptibility to peer pressure. The findings also highlighted the moderating effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…However, only Mills’ (2003) study included fathers, and although several studies incorporated observational and questionnaire methods similar to ours, the particular measures used were different than the present study. Our findings may be consistent with studies finding that parental indifference is linked to children’s difficulties with self-conscious emotions (Claesson & Sohlberg 2002; Gilbert, Cheung, Grandfield, Campey, & Irons, 2003; Han & Kim 2012). In addition, Kochanska et al (2002) reported that children of mothers who used more assertive parenting were less prone to guilt than other children, suggesting that a more permissive parenting style may have the reverse impact.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, only Mills’ (2003) study included fathers, and although several studies incorporated observational and questionnaire methods similar to ours, the particular measures used were different than the present study. Our findings may be consistent with studies finding that parental indifference is linked to children’s difficulties with self-conscious emotions (Claesson & Sohlberg 2002; Gilbert, Cheung, Grandfield, Campey, & Irons, 2003; Han & Kim 2012). In addition, Kochanska et al (2002) reported that children of mothers who used more assertive parenting were less prone to guilt than other children, suggesting that a more permissive parenting style may have the reverse impact.…”
Section: Discussionsupporting
confidence: 93%
“…Retrospective studies of caregiving in childhood found that adults who reported receiving low parental caring and attention, and greater indifference and rejection were more prone to feel shame (Claesson & Sohlberg, 2002; Gilbert, Allan, & Goss, 1996; Lutwak & Ferrari, 1997). Studies with toddlers (Kelley, Brownell, & Campbell, 2000) and older children (Han & Kim, 2012; Stuewig & McCloskey, 2005) also suggest that negative and rejecting parents who provide little positive feedback have children at increased risk for shame expression. However, there have been few prospective longitudinal studies examining associations between parenting and children’s shame and guilt.…”
mentioning
confidence: 99%
“…Some studies have suggested that violent families are more likely to be characterized by negative parenting behaviors that contribute to children's experiencing debilitating levels of shame (Bennett et al 2005;Stuewig and McCloskey 2005). Cross-sectional and prospective studies with children and adolescents suggest that feelings of shame are associated with parental indifference, rejection, and abandonment (Han and Kim 2012), authoritarian parenting style (Mills 2003), parental conditional positive regard (Assor and Tal 2012), and devaluation and overt shaming (Mills et al 2010). The use of verbal disapproval, hostility, contempt, and physical abuse poses a serious threat to children's self-esteem as it conveys a strong message that they fail to live up to parental expectations and are a disappointment and unlovable as persons (Feiring 2005).…”
Section: Exposure To Intimate Partner Violence and Self-esteemmentioning
confidence: 99%
“…That is, research suggests that negative parental rearing behaviors play a role in children’s proneness to experience shame. More specific, data from both retrospective studies with adults and cross-sectional and longitudinal studies with children and adolescents have shown that shame is positively connected with an authoritarian parenting style (Mills 2003), denigration, indifference, rejection, and abandonment of parents (Claesson and Sohlberg 2002; Gilbert et al 2003; Han and Kim 2012; Harvey et al 1997), parental use of conditional positive regard (Assor and Tal 2012), parentification (Wells and Jones 2000), negative parental evaluative behavior (Alessandri and Lewis 1993), and disparagement and shaming (Gilbert et al 1996; Mills et al 2010). …”
Section: Introductionmentioning
confidence: 99%